PENINGKATAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR MELALUI PENDEKATAN KONSTRUKTIVISME - Ayu Ningsih Almirus; Trinindi Eriswan Fitri; Amin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The reserach is motivated by learning process was still not student-centered. This research was conducted in fifth grade at SDN 20 Jalamu and SDN 31 Limau Manis Pesisir Selatan. The purpose of this research was to research of improvement student learning outcomes at mathematic by using a constructivism approach to learning with those using conventional mathematics learning. This study used a interviews, questionnaires and observation sheets. This research was conducted by pretest and posttest. The students answer were analyzed using student learn outcome in the low, medium, and high group in the experimental class and control class. The result of the research indicated that the improved of student learning outcomes in the experimental class about 0,68, but improved of student learning outcomes in the control class about 0,07. So it can be concluded that the constructivism approach can improve student learning outcomes of mathematics.